2006
DOI: 10.1007/s00192-006-0190-y
|View full text |Cite
|
Sign up to set email alerts
|

Is single-dose fosfomycin trometamol a good alternative for asymptomatic bacteriuria in the second trimesterof pregnancy?

Abstract: Untreated asymptomatic bacteriuria has been associated with acute pyelonephritis, which may have a role in many maternal and fetal complications. Acute pyelonephritis in pregnancy is related to anemia, septicemia, transient renal dysfunction, and pulmonary insufficiency. A randomized study was conducted to assess the clinical and microbiological efficacy of a single dose of fosfomycin trometamol for the treatment of asymptomatic bacteriuria in the second trimester of pregnancy compared with a 5-day regimen of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 26 publications
2
41
1
5
Order By: Relevance
“…Two studies (Bayrak 2007;Campbell-Brown 1987) compared cephalosporins (secondgeneration cefuroxime and first-generation cephalexin) with antibiotics less associated with E. coli resistant strains, fosfomycin trometamol and pivampicillin/pivmecillinam (Miraxid®), all of which belong to pregnancy category B. Both studies, however, failed to demonstrate any significant difference in efficacy between the cephalosporins and the latter two antibiotics.…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies (Bayrak 2007;Campbell-Brown 1987) compared cephalosporins (secondgeneration cefuroxime and first-generation cephalexin) with antibiotics less associated with E. coli resistant strains, fosfomycin trometamol and pivampicillin/pivmecillinam (Miraxid®), all of which belong to pregnancy category B. Both studies, however, failed to demonstrate any significant difference in efficacy between the cephalosporins and the latter two antibiotics.…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
“…Antibiotic resistance to ampicillin is increasing (Bayrak 2007). Pivmecillinam, despite belonging to the same family of antibiotics was able to retain its activity against E. coli (Bint 1979).…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
“…It has higher efficacy and better compliance over Nitofurantoin and other drugs making it a first choice drug for uncomplicated UTIs In pregnancy [10] Mody et al (2014). [48] The minor side effects of Fosfomycin were confirmed by Bayrak et al (2007), who revealed associated minor side effects with Fosfomycin [45].…”
Section: Discussionmentioning
confidence: 99%
“…55,199 More recently, it has been compared with ceftibuten 400 mg once daily for three days, with a 95% therapeutic success rate (clinical cure and bacteriological eradication). 206 In the treatment of asymptomatic bacteriuria, a single dose of fosfomycin trometamine showed the same level of therapeutic success as cefuroxime axetyl for five days (93.2% versus 95%), 207 and as amoxicillin + clavulanic acid for seven days (eradication rate over 80% in both groups). 208 A single 2 g dose of fosfomycin trometamine was also compared with pipemidic acid 200 mg twice daily for seven days in children weighing more than 25 kg.…”
Section: Clinical Studiesmentioning
confidence: 94%